Pengaruh Metode Pembelajaran Bermain Peran terhadap Kemampuan Berbicara Kelas 3 MIN 3 Kepulauan Selayar - Elsa Krisnawati; Muh. Akhir; Sri Rahayu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The main problem in this research is how the application of the role playing method affects the learning outcomes of speaking skills for class III MIN 3 Selayar Islands. This research aims to determine the effect of applying the role-playing method on the speaking skills learning outcomes for class III MIN 3 Selayar Islands. This research uses a quantitative approach with an experimental type of research, meaning the experimental method is to study the influence of certain variables on other variables, through trials. under specially created conditions. To analyze the data that will be obtained from the research results, descriptive and inferential statistical analysis will be used. The data collected in the form of pretest scores and posttest scores were then compared. The results of the research show that Ho is rejected and H1 is accepted, meaning that there is an influence of the use of the role-playing method on the speaking ability of Class 3 MIN 3 Selayar Islands students. The test results show that there are differences in scores in students' speaking abilities before and after learning the role-playing method. The average value of students before and after using different role playing methods.